(untitled) (CIPEEX, 2026)
Femoral neck fractures in elderly people are prevalent injuries, often resulting from falls and having a high impact on the patient’s functionality and quality of life. They represent a serious public health problem due to the high economic costs of treatment and its consequences, in addition to the elevated morbidity and mortality rates. Guidelines for femoral fracture management recommend that surgeries be performed as soon as possible, taking into account the health condition of the elderly patient. The objective was to analyze the effects of rehabilitation in elderly patients who underwent surgery for extracapsular femoral neck fracture, considering the biopsychosocial aspects and the individuality of each patient in the context of aging. This is an Integrative Literature Review (ILR), descriptive in nature, with a qualitative approach, based on searches in the Virtual Health Library (VHL), Scielo, PubMed, and Scopus databases, covering publications from 2020 to 2025. The results indicate that rehabilitation is essential to restore mobility, muscle strength, and independence in elderly patients, reducing the risks of complications such as muscle loss, physical deconditioning, and dependence on long-term care. It is concluded that early and continuous rehabilitation is fundamental for the recovery of elderly patients after extracapsular femoral neck fracture, proving effective in both conservative and surgical approaches. This process not only accelerates functional recovery but also makes it more efficient and less painful, promoting healthy and dignified aging.